Focus on the world's poorest and hungry people: IFPRI 2006-2007 Annual Report Essay - von Braun, Joachim (International Food Policy Research Institute, 2007)
If economic growth alone could rapidly reduce poverty and hunger, many parts of the developing world ought to be much freer from these scourges than they are. To be sure, rapid economic growth in many developing countries, and agricultural growth in particular, has advanced global progress in reducing poverty and hunger. But even growth that reduces poverty has its limits in reaching and including extremely poor and hungry people. Especially in environments of high inequality and poor governance, growth often does little to improve the livelihoods of those at the bottom of the income scale. And while growth is key to cutting poverty initially, its power to reduce poverty and the dangers to human well-being—such as childhood malnutrition—diminishes as poverty reduction progresses.